Antibacterial activity of Moroccan Zantaz Honey and the influence of its physicochemical parameters using chemometric tools - Elamine, Youssef (2021)
The emergence of multidrug-resistant bacteria has prompted the development of alternative therapies, including the use of natural products with antibacterial properties. The antibacterial properties of Zantaz honey produced in the Moroccan Atlas Mountains against Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus was evaluated and analyzed using chemometric tools. Minimum inhibitory concentration (MIC) and Minimum bactericidal concentration (MBC) against S. aureus were the lowest (112.5 ± 54.5 mg/mL), revealing that this species was most sensitive to Zantaz honey. P. aeruginosa showed an intermediate sensitivity (MIC= 118.75 ± 51.9 mg/mL), while E. coli was the most resistant to treatment (MIC = 175 ± 61.2 mg/mL). Content of monosaccharides, certain minerals, and phenolic compounds correlated with antibacterial activity (p < 0.05). Principal component analysis of physicochemical characteristics and antibacterial activity indicated that the parameters most associated with antibacterial activity were color, acidity, and content of melanoidins, fructose, epicatechin, methyl syringate, 4-coumaric acid, and 3-coumaric acid.